Severe Maternal Morbidity and Maternal Mortality: What Can be Learned From Reviewing Near Miss and Adverse Events?. Issue 4 (July 2018) - Simpson, Kathleen Rice
Abstract : Severe maternal morbidity and maternal mortality cases require thorough review by an interdisciplinary quality committee. Lessons learned can be used to enhance care and develop strategies for prevention of these types of adverse events.